IMPLEMENTASIPERATURAN DAERAH NOMOR 18 TAHUN 2009 TENTANG PENYELENGGARAANADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN CATATAN SIPILKABUPATEN KETAPANG - Rini Novianti E42008024 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2013)
The implementation about the recording of wisdom for the birth certificategives problem, for last three years (2009-2012) the number of the owner of thebirth certificate is only 20%. The purpose of this research is showing how theprocess of the implementation about the wisdom of the birth recording and theobstacle which cause how difficult to record. The result of the research showsthe implementation has been done well, it is seen from the socialisation thathave done, the good of organization structure, the relation between theorganization and the good character of organization. So, the things that causethe number of the owner of the birth certificate get low is not from theimplementation, but it is because of the public itself.Keywords : Implementation, Birth Recording, Birth Certificate